Literatur Review: Kontribusi Teknologi Finansial Terhadap Inklusi Keuangan Digital Di Era Ekonomi Digital - Ferdy Faith Christ Waruwu; Gilbred Bonar Sinaga; Herikson Muksa PutraSitanggang (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The rapid development of financial technology (fintech) has become a key driver of transformation in the financial sector worldwide, particularly in promoting digital financial inclusion. Financial inclusion is a crucial component of sustainable economic development, as it provides access to formal financial services for underserved and unbanked populations. This study aims to examine and analyze findings from ten national and international scholarly journals published within the last five years (2020–2025) regarding the contribution of fintech to financial inclusion. A systematic literature review method is employed, focusing on how fintech enhances financial literacy, expands service outreach, and promotes efficiency and innovation in digital financial systems. The findings reveal that fintech consistently contributes positively to improving access to and quality of financial services, particularly among vulnerable populations and regions not yet served by traditional financial institutions. These findings highlight the urgency of formulating supportive policies that foster an inclusive and sustainable fintech ecosystem.